2005
DOI: 10.1073/pnas.0406632102
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin2, interacting with phosphodiesterase 4, regulates synaptic release probability and presynaptic inhibition by opioids

Abstract: Most -opioid receptor agonists recruit ␤-arrestin2, with some exceptions such as morphine. Surprisingly, however, the acute analgesic effect of morphine is enhanced in the absence of ␤-arrestin2. To resolve this paradox, we examined the effects of morphine and fentanyl in acute brain slices of the locus coeruleus and the periaqueductal gray from ␤-arrestin2 knockout mice. We report that, in these mice, presynaptic inhibition of evoked inhibitory postsynaptic currents was enhanced, whereas postsynaptic G protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Mice lacking b-arrestin2 also display increased GTPgS binding in PAG membranes without a change in m-opioid receptor density (Bohn et al, 1999(Bohn et al, , 2000. Although acute postsynaptic sensitivity of m-opioid receptor activation of GIRK channels has been reported to be the same in barrestin2 knock-out and wild-type mice (Bradaia et al, 2005), m-opioid receptor supersensitivity may only occur after prolonged, or repeated morphine treatment and not with acute administration.…”
Section: Discussionmentioning
confidence: 97%
“…Mice lacking b-arrestin2 also display increased GTPgS binding in PAG membranes without a change in m-opioid receptor density (Bohn et al, 1999(Bohn et al, , 2000. Although acute postsynaptic sensitivity of m-opioid receptor activation of GIRK channels has been reported to be the same in barrestin2 knock-out and wild-type mice (Bradaia et al, 2005), m-opioid receptor supersensitivity may only occur after prolonged, or repeated morphine treatment and not with acute administration.…”
Section: Discussionmentioning
confidence: 97%
“…␤-Arrestin 2 knockout mice exhibit several phenotypes associated with neuronal signaling such as enhanced sensitivity to morphine in pain assays (31), enhanced reward response to opioids (32), and decrease in dopaminemediated locomotor responses (33). Through interaction with phosphodiesterase 4, ␤-arrestin 2 regulates opioid-mediated presynaptic inhibition by regulating synaptic release probability (34). Recently it has been shown that ␤-arrestin 2 associates with Akt and phosphatase PP2A to mediate dopaminergic responses (33).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase-4 (PDE4), an enzyme that specifically catalyzes the hydrolysis of cyclic AMP (cAMP) and is critical in controlling its intracellular concentration, is involved in various central nervous system (CNS) processes, including depression , learning and memory (Barad et al, 1998), anxiety (Beer et al, 1972), and analgesia (Bradaia et al, 2005). Administration of PDE4 inhibitors such as rolipram produces antidepressant-like effects (Zhang et al, 2002(Zhang et al, , 2006, reverses memory deficits induced pharmacologically, physically, or genetically (Bourtchouladze et al, 2003;Imanishi et al, 1997;Zhang et al, 2000Zhang et al, , 2004, alters anxiogenic-like behavior (Imaizumi et al, 1994;Silvestre et al, 1999a), and induces analgesia in rodents (Kumar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%